High-throughput synthesis and strengthening behavior of Fex(CoCrNi)100-x medium-entropy alloys via laser-direct energy deposition - Yu Liao; Yisi Song; Mengyao Zheng; Hao Zhang; Beier Sun; Yunjiao Niu; Chuanwei Li; Jianfeng Gu (Materials Research Letters)
Compositionally graded Fex(CoCrNi)100-x medium-entropy alloys (MEAs) were fabricated via laser-direct energy deposition. The effects of Fe content and heat treatment on microstructure, mechanical properties, and strengthening behavior were investigated. Increasing Fe content led to a phase transition from FCC to BCC, enabling varied combinations of hardness and ductility. Quenching improved the hardness due to the enhanced martensitic matrix strengthening, while tempering promoted the formation of Cr-rich nano-clusters, further improving the hardness. Our study provides valuable insights into the design of low-cost and high-performance ferrous MEAs (Fe-MEAs) and offers a reproducible framework for developing other high-property alloy systems.